Effect of Mode of Delivery on Cord Blood Thyroid Stimulating Hormone Levels- A Cross-sectional Study - Roshni Gurnani; Madhuri Bhagwan Engade; Haseeb Mohammed; Saranya Murlidharan Sindhu; Mahafrin Homar Goiporia; Arti Subesingh Choudhary (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Cord Blood Thyroid Stimulating Hormone (CBTSH) level estimation is an accepted screening tool for Congenital Hypothyroidism (CH). CBTSH levels are affected by many perinatal factors including mode of delivery. Previous studies have shown conflicting results on effect of mode of delivery on CBTSH levels. Aim: To study CBTSH profile in neonates born at tertiary care referral centre and to analyse the influence of mode of delivery (vaginal vs caesarean) on CBTSH levels. Materials and Methods: This was a cross-sectional study conducted at Mahatma Gandhi Medical College and Hospital from February 2014 to August 2015. Study population included 856 neonates (males=437, females=419). The CBTSH levels were estimated using electrochemiluminescence immunoassay 'ECLIA' on the elecsys 2010 analyser. CBTSH levels between vaginally delivered and caesarean section born babies were compared. The values were tabulated as mean and statistically analysed using Statistical Package for the Social Sciences (SPSS) software version 21. Results: Mean CBTSH level of vaginally born neonates were 9.59 (median 7.0) in comparison to 9.11(median7.15) in caesarean born babies, this difference was not statistically significant. Conclusion: As per the present study finding mode of delivery did not have any significant effect on CBTSH levels.